Aberrant microRNA expression in multiple myeloma. (5th June 2013) - Dimopoulos, Konstantinos; Gimsing, Peter; Grønbæk, Kirsten
Abstract Multiple myeloma (MM) is a devastating disease with a complex biology, and in spite of improved survivability by novel treatment strategies over the last decade, MM is still incurable by current therapy. MicroRNAs (miRNAs) are small, non‐coding RNA molecules that regulate gene expression at a post‐transcriptional level. More than half of all protein coding genes are estimated to be controlled by miRNAs, and their expression is frequently deregulated in many diseases, including cancer. Recent studies have reported aberrant miRNA expression patterns in MM, and the function of individual miRNAs in MM has been investigated in detail in cell culture and animal models. Here, we review the current knowledge on the role of miRNAs in MM pathogenesis and discuss their potential as prognostic biomarkers and targets for treatment.